Impact of Heavy Metal Stress on Antioxidant Mechanisms of Avicennia marina (Forsk.) and Rhizophora mucronata Lamk.: Antioxidant of Avicennia marina (Forsk.) (Biological Sciences - PJSIR, 2021)
Mangrove species are growing in exposed areas which have heavy metal contamination. The safeguard the mangrove ecosystem, it is important to understand their antioxidant responses to heavy metal toxicity. The goal of this study was to determine the effect of multi-heavy metals i.e. (Pb, Cd, Cr and Hg) on two mangrove plants Avicennia marina and Rhizophora mucronata of Indus delta via investigating their antioxidative defence mechanism of leaves and roots. In this regard mangrove seedlings of both species were treated with five different concentrations of four heavy metals and different time durations (15, 30, 45 and 60 days) for ascorbate peroxidase, catalase and superoxide dismutase in leaves and root tissues. The findings indicate that the heavy metals have significantly altered the antioxidant enzyme activities with respect of metals concentration and duration of exposure. With extended exposure higher antioxidant activities was observed in metal treated roots and leaves at higher concentrations. A pronounced stimulation (P